Índice de governança corporativa : variação das empresas brasileiras em função das expectativas de mercado - Domingos, André Luis Reis Dima (2009)
The concepts of Corporate Governance are not new, but the severity of financiai impacts caused by corporate scandals encourages companies to adopt better standards of governance. Professional investors are willing to pay a premium to invest in companies with high governance standards and ensure a favorable corporate environment regarding the return on their investment. The worldwide liquidity which the world has experienced in recent years has provided an increasing amount of resources, not only for Brazil but for most emerging markets, for local capital markets and direct investments. This capital, largely externai, needs transparency, regulation and other requirements in order to reduce the risks associated with target companies. Based on market expectations of macroeconomic indicators provided by the System Market Expectations of the Central Bank of Brazil and the information provided by the Bovespa and its market indexes Ibovespa and IGC, this study sought an association between changes in these expectations and appreciation or depreciation of average market capitalization and stock index - Ibovespa and IGC. It was observed that both the Ibovespa and the IGC and the mean market capitalization of the Bovespa and Ibovespa subject to the same influences of national macroeconomic variables, but in different magnitudes. However, it was made as an exception, the mean market capitalization of the IGC, which is influenced by different macroeconomic expectations.